Heart disease prediction using techniques of classification in machine learning - Afrose, Sadia; Rubaiat, Farah; Tabassum, Homayra (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.